Genome-Wide Identification of Xyloglucan Endotransglucosylase/Hydrolase Multigene Family in Chinese Jujube (Ziziphus jujuba) and Their Expression Patterns Under Different Environmental Stresses - Mohamed Refaiy; Muhammad Tahir; Lijun Jiao; Xiuli Zhang; Huicheng Zhang; Yuhan Chen; Yaru Xu; Shuang Song; Xiaoming Pang (Plants, 2024)
The Xyloglucan endotransglucosylase/hydrolase (XTH) family, a group of cell wall-modifying enzymes, plays crucial roles in plant growth, development, and stress adaptation. The quality and yield of Chinese jujube (Ziziphus jujuba) fruit are significantly impacted by environmental stresses, including excessive salinity, drought, freezing, and disease. However, there has been no report of the XTH encoding genes present in the Chinese jujube genome and their response transcription level under various stresses. This study provides an in-depth analysis of ZjXTH genes in the genome of Chinese jujube and elucidates their structural motifs, regulatory networks, and expression patterns under various stresses. A total of 29 ZjXTH genes were identified from the Ziziphus jujuba genome. Phylogenetic analysis classifies ZjXTH genes into four distinct groups, while conserved motifs and domain analyses reveal coordinated xyloglucan modifications, highlighting key shared motifs and domains. Interaction network predictions suggest that ZjXTHs may interact with proteins such as Expansin-B1 (EXPB1) and Pectin Methylesterase 22 (PME22). Additionally, cis-regulatory element analysis enhances our understanding of Chinese jujube plant’s defensive systems, where TCA- and TGACG-motifs process environmental cues and orchestrate stress responses. Expression profiling revealed that ZjXTH1 and ZjXTH5 were significantly upregulated under salt, drought, freezing, and phytoplasma infection, indicating their involvement in biotic and abiotic stress responses. Collectively, these findings deepen our understanding of the functional roles of Chinese jujube XTHs, emphasizing their regulatory function in adaptive responses in Chinese jujube plants.